2019
DOI: 10.1037/pag0000391
|View full text |Cite
|
Sign up to set email alerts
|

Aging and feature-binding in visual working memory: The role of verbal rehearsal.

Abstract: Age-related decline in ability to bind and remember conjunctions of features has been proposed as an explanation for the pronounced decline of visual Working Memory (WM) in healthy aging. However, evidence that older adults exhibit greater visual feature binding deficits than younger adults has been mixed. Binding deficits in older adults are often observed using paradigms with easy-to-label features. Labeling and rehearsing single features may result in apparent binding deficits if older adults rely on compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 131 publications
2
17
0
Order By: Relevance
“…Similarly, more older than younger adults in our uninstructed control group reported using a sub-vocal Rehearsal strategy, that is, silent repetition of verbal labels for material to be recalled (see Logie et al, 1996 ; Wang et al, 2016 ). Specifically, 4 younger and 25 older adults used this strategy in the three N-back tasks combined (see Figure 4 ), supporting previous suggestions that older adults may rely more on verbal rehearsal even in visual WM tasks ( Forsberg et al, 2019 ). More severe WM deficits for visuospatial material than for verbal material have been observed in older adults (e.g., Jenkins et al, 1999 ; Leonards et al, 2002 ; Myerson et al, 1999 ), and perhaps sub-vocal rehearsal can be used to compensate for declining visual memory.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, more older than younger adults in our uninstructed control group reported using a sub-vocal Rehearsal strategy, that is, silent repetition of verbal labels for material to be recalled (see Logie et al, 1996 ; Wang et al, 2016 ). Specifically, 4 younger and 25 older adults used this strategy in the three N-back tasks combined (see Figure 4 ), supporting previous suggestions that older adults may rely more on verbal rehearsal even in visual WM tasks ( Forsberg et al, 2019 ). More severe WM deficits for visuospatial material than for verbal material have been observed in older adults (e.g., Jenkins et al, 1999 ; Leonards et al, 2002 ; Myerson et al, 1999 ), and perhaps sub-vocal rehearsal can be used to compensate for declining visual memory.…”
Section: Discussionsupporting
confidence: 83%
“…Specifically, work from our group found that older adults associated labels based on their familiarity to abstract shapes in the memory array of a shape CD task and relied on rehearsal to compare shapes across the memory and test arrays (Wijeakumar, Magnotta, et al, 2017a). Our findings are supported by recent work from Logie and colleagues, who suggest that age-related changes in VWM might reflect the difficulty in actively engaging cognitive systems required to employ strategies to successfully perform the task (Forsberg, Johnson, & Logie, 2019;Logie, 2018;Logie, Belletier, & Doherty, in press). These findings in older adults defend the dependence of WM processes on LTM.…”
Section: The Association Between Wm and Long-term Memory (Ltm) Processupporting
confidence: 79%
“…The Strength model might represent brain mechanisms in older adults who recruit verbal strategies, resulting in quicker consolidation of items in the WM field. However, in general, such reliance is still indicative of age-related decline because it relies on extra resources to complete the task (Forsberg, Johnson, & Logie, 2019;Wijeakumar, Magnotta, et al, 2017a). On the other hand, the Width model might represent a different form of age-related decline, where defecits in perceptual processes result in longer decay times for peaks in the CON field.…”
Section: {Insert Figure 10}mentioning
confidence: 99%
“…If visual tasks allow verbal labeling of stimuli, and younger and older adults differ in the extent to which they rely on such labeling, problematic confounds likely occur—especially if visual WM paradigms used to measure a given phenomenon differ in the extent to which verbalization is possible. For instance, age-related differences in verbal recoding could be problematic in paradigms measuring visual feature-binding if single features lend themselves to efficient verbal labeling and rehearsal and bound objects do not—while ‘red, blue, green’ may be feasible to verbalize during a typical memory retention interval, ‘red-circle, blue-square, green-triangle’ would likely be much more cumbersome (Brockmole & Logie, 2013 ; see Forsberg, Johnson, & Logie, 2019 , for a summary of feature-binding paradigms and the role of verbal labeling, but see also Sense, Morey, Prince, Heathcote, & Morey, 2016 ). Indeed, age-related binding deficits in delayed estimation tasks were observed in some experimental settings (memory for color and orientation of bars; Peich et al, 2013 ), but not others (locations of complex, hard-to-name fractal objects; Pertzov, Heider, Liang, & Husain, 2015 ).…”
mentioning
confidence: 99%